Organizational climate and its relationship with the work performance of administrative workers at the private university San Carlos 2020 - Choquejahua Olivera, Lizbet (2022)
The research called "Organizational Climate and its relationship with the job performance of administrative workers at the San Carlos Private University, 2020". with general objective: Establish the relationship between the organizational climate and work performance in administrative workers of the University. And specific objectives: Identify the relationship that exists between motivation and job performance in administrative workers at UPSC Puno 2020. And determine the relationship that exists between social relationships with the job performance of administrative workers at UPSC Puno 2020. With general hypothesis: There is a significant relationship between the organizational climate and job performance in administrative workers. Regarding the methodology, the type of research is of a quantitative approach, it has the Hypothetical - deductive method, with a non-experimental and cross-sectional design. The study population was 92 administrative workers, with a non-probabilistic sample because we worked with the entire population. For data collection, the survey will be used as a technique and the questionnaire on a Likert scale as a tool. The results indicate that 46.7% of administrative workers show a high level of organizational climate and a high level of performance. There is a significance p=0.00, which is less than p=0.01, and r=0.968, which corresponds to a very high correlation, accepting the alternative hypothesis. In conclusion, the organizational climate is significantly related to job performance in administrative workers at the Universidad Privada San Carlos Puno 2020.